Frequency dependence of photoelectron angular distributions in small Na clusters - Wopperer, P.; Dinh, P. M.; Suraud, E.; Reinhard, Paul-Gerhard (Physical Review A - Atomic, Molecular, and Optical Physics, 2012)
We investigate from a theoretical perspective photoelectron angular distributions (PADs) in small Na clusters in relation to recently available experimental results. We consider various (increasingly refined) levels of theory in order to better understand relevant physical trends. It is found that PADs are extremely sensitive to all details of the modeling such that a detailed description of the final state and the ionic background is necessary. Finally, we compare the theoretical description with recent experimental data on the cluster anion Na7- and find a satisfying agreement for full time-dependent local-density approximation (TDLDA) with ionic background. © 2012 American Physical Society.
CRIS-Team Scopus Importer:2023-07-24